2022
DOI: 10.1159/000521792
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vascular Loops in the Cerebellopontine Angle on Audio-Vestibular Symptoms: A Systematic Review

Abstract: It has been suggested that vascular loops in the cerebellopontine angle and internal auditory canal are involved in the etiology of audio-vestibular symptoms. Several studies have focused on the compression of the eighth cranial nerve by vascular loops but have yielded contradictory results regarding their clinical significance. The aim of this study was to investigate whether vascular loops in this region correlate with audio-vestibular symptoms and which loop features – if any – can potentially lead to sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Attempts have been made to elucidate the exact pathophysiology of SNHL/tinnitus caused by vascular loops, with theories including direct compression of the nerve by the loop, demyelination of the nerve due to contact with the artery, and reduced perfusion leading to hypoxia of the nerve [13][14]. In the present study, no obvious compression of the vestibulocochlear nerve indicates that the symptoms may have been caused by hypoxia or micro compression.…”
Section: Discussionmentioning
confidence: 50%
“…Attempts have been made to elucidate the exact pathophysiology of SNHL/tinnitus caused by vascular loops, with theories including direct compression of the nerve by the loop, demyelination of the nerve due to contact with the artery, and reduced perfusion leading to hypoxia of the nerve [13][14]. In the present study, no obvious compression of the vestibulocochlear nerve indicates that the symptoms may have been caused by hypoxia or micro compression.…”
Section: Discussionmentioning
confidence: 50%
“…The presence of vascular loop in the CPA-IAC region is not included in any diagnostic criteria for vestibular disorders except for vestibular paroxysmia (VP) [ 20 ], in which the neurovascular compression has been considered as the underlying mechanism. In fact, due to the lack of objective diagnostic test, vascular compression is a diagnosis of exclusion and patients with this syndrome are often misdiagnosed [ 3 , 5 ]. The causal relationship between audio-vestibular symptom and the presence of vascular loops in CPA-IAC region is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that imaging findings based on the Kazawa classification system did not correlate with the lateralization, Ménière’s stage, EcochG, and caloric test findings in unilateral MD, which is in line with the results of a systematic review. Papadopoulou et al included 15 studies for systematic review and found that, the radiological results did not consistently correlate with audio-vestibular symptoms in about 70% of the included patients, suggesting that vascular loops may be an anatomical variant in a significant majority of cases [ 3 ]. Of note, the etiologies underlying these audio-vestibular symptoms were undefined in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations